Estimating the Effect of Nonresponse Bias in a Survey of Hospital Organizations. (September 2013) - Lewis, Emily F.; Hardy, Maryann; Snaith, Beverly
Nonresponse bias in survey research can result in misleading or inaccurate findings and assessment of nonresponse bias is advocated to determine response sample representativeness. Four methods of assessing nonresponse bias (analysis of known characteristics of a population, subsampling of nonresponders, wave analysis, and linear extrapolation) were applied to the results of a postal survey of U.K. hospital organizations. The purpose was to establish whether validated methods for assessing nonresponse bias at the individual level can be successfully applied to an organizational level survey. The aim of the initial survey was to investigate trends in the implementation of radiographer abnormality detection schemes, and a response rate of 63.7% (325/510) was achieved. This study identified conflicting trends in the outcomes of analysis of nonresponse bias between the different methods applied and we were unable to validate the continuum of resistance theory as applied to organizational survey data. Further work is required to ensure established nonresponse bias analysis approaches can be successfully applied to organizational survey data. Until then, it is suggested that a combination of methods should be used to enhance the rigor of survey analysis.